The ontological (in)security of similarity: Wahhabism versus Islamism in Saudi foreign policy - Darwich, May (GIGA working papers, 2014)
It has long been argued that identity matters in international relations. Yet, how identity impacts enmity and conflict among states remains the subject of debate. The existing literature asserts that differences in identity can be a source of conflict, whereas convergence and similarity lead to cooperation. Nevertheless, empirical evidence from the Middle East has long defied this hypothesis. The Kingdom of Saudi Arabia, which prides itself on being an Islamic model and claims Islamic leadership, has opposed the rise to power of Islamist movements in the Middle East. To address this paradox, this article builds on the growing literature on ontological security to propose a theoretical framework explaining how similarity can generate anxiety and identity risks. This framework, I argue, moves beyond traditional regime-security approaches to reveal that security is not only physical but also ontological. I then illustrate the argument through a comparison of Saudi identity risks in the wake of the Iranian revolution (1979) and the ascendance of the Muslim Brotherhood to power in Egypt (2012). Ultimately, these cases provide intriguing insights into foreign policy behaviour during critical situations.